Biomechanical comparison of fixation systems in posterior wall fracture of acetabular by finite element analysis. Issue 1 (1st January 2016) - Lei, Jianyin; Liu, Haibo; Li, Zhiqiang; Wang, Zhihua; Liu, Ximing; Zhao, Longmao
Abstract: Background: The use of reconstruction plates and lag screws has been recommended for fractures to the posterior wall of the acetabulum. However, little information about the rigidity of recommended forms of fracture fixation is available. This study aimed to evaluate the biomechanical difference among the fixation systems. Methods: A posterior wall fracture, which is represented by softer elements with lower elastic modulus, was created along an arc of 40–90° about the acetabular rim. Three different fixation systems: screws alone, reconstruction plate with screws, reconstruction plate with T-shaped plates were used to fix the posterior wall fractures to the acetabulum. Results: All three fixation system can be used to obtain good functional outcomes. The reconstruction plate with T-shaped plates was beneficial to increasing the effective stiffness, decreasing the stress concentration and enhancing the rigidity of fracture fixation. So this fixation system served an ideal result in the analysis. Conclusion: Theoretically, the reconstruction plate with T-shaped plates system may reduce many of the risks and limitations compared to the other fixation systems. This fixation system may result in a clinical benefit.